School absenteeism during menstruation amongst adolescent girls in Delhi, India - Vashisht, Aditi (J Family Community Med, 2018)
BACKGROUND: Girls' health and education form the cornerstone of development and the gateway to full participation as women in political, economic, and cultural life of a country. Poor menstrual hygiene management has been shown to result in a sense of shame, anxiety, and embarrassment that contributes to absenteeism and poor performance at school. The objectives of this study were to determine the percentage of girls absent from school during menstruation, to evaluate the various factors associated with school absenteeism during menstruation, and to assess the practices regarding menstrual hygiene. MATERIALS AND METHODS: A mixed method research of combined cross-sectional study and qualitative research was conducted in six government schools of Delhi by means of a questionnaire survey and focus group discussions. The sample size was 600 adolescent girls. RESULTS: Out of 600, 245 (40%) girls remained absent from school during their menstruation. School absenteeism was significantly associated with the type of absorbent used, lack of privacy at school, restrictions imposed on girls during menstruation, mother's education, and source of information on menstruation. Nearly 65% reported that it affected their daily activities at school and that they had to miss their class tests and classes as a result of pain, anxiety, shame, anxiety about leakage, and staining of their uniform. CONCLUSION: Since mothers are the primary source of information, they should be counseled to dispose of their taboos about discussing issues related to menstruation. They should be taught about the ill effects of adhering to taboos related to menstruation. The curriculum on general biology should have more detail on menstruation.